The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1183/13993003.01526-2020
|View full text |Cite
|
Sign up to set email alerts
|

Distinct features of SARS-CoV-2-specific IgA response in COVID-19 patients

Abstract: In comparison to severe acute respiratory syndrome coronavirus (SARS-CoV), SARS-CoV-2 appears to be more contagious [1], and coronavirus disease 2019 (COVID-19) patients demonstrate varied clinical manifestations distinct from those seen in patients with SARS-CoV and Middle East respiratory syndrome coronavirus infections [2]. Collective results from the clinical and epidemiological observations suggest a distinct viral-host interaction in COVID-19 patients. Profiling of the antibody response during SARS-CoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
340
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(388 citation statements)
references
References 14 publications
34
340
1
13
Order By: Relevance
“…An early study of 173 patients with SARS-CoV-2 infection showed seroconversion in 93% of patient with an average time of 11 days [ 13 ]. Similar results are reported in other serological studies showing high seroconversion rates between 10 and 14 days after symptoms onset [ [14] , [15] , [16] , [17] ]. Antibody response peak between the second and third-week after infection declining afterwards [ 13 , 18 ] and is characterized by the presence of IgA, IgM and IgG in plasma and saliva [ 13 , 14 , 18 , 19 ].…”
Section: Humoral Responses Against Sars-cov-2supporting
confidence: 91%
“…An early study of 173 patients with SARS-CoV-2 infection showed seroconversion in 93% of patient with an average time of 11 days [ 13 ]. Similar results are reported in other serological studies showing high seroconversion rates between 10 and 14 days after symptoms onset [ [14] , [15] , [16] , [17] ]. Antibody response peak between the second and third-week after infection declining afterwards [ 13 , 18 ] and is characterized by the presence of IgA, IgM and IgG in plasma and saliva [ 13 , 14 , 18 , 19 ].…”
Section: Humoral Responses Against Sars-cov-2supporting
confidence: 91%
“…This is not on par with the dynamic regularity of antibodies in other viral infection. Many similar results have reported that the serum antibodies dynamic of this novel virus surprised all of us 17,[21][22][23] .We also found that without breast feeding, the maternal protective effect in infants was rapidly eliminated naturally within two months after birth ( Table 3). It is worth noting that this rate of decline was beyond expectations.…”
Section: Resultssupporting
confidence: 75%
“…Systemic IgA responses may play a relevant role in the pathogenesis of COVID-19. 38 Mucosal IgA likely exerts a protective role by preventing SARS-CoV-2 adherence to epithelial cells. Circulatory IgA may also contribute to SARS-CoV-2 neutralization.…”
Section: What Is the Role Of Iga In Sars-cov-2 Infection?mentioning
confidence: 99%